2019
DOI: 10.1111/acer.13931
|View full text |Cite
|
Sign up to set email alerts
|

Brain Glutamate, GABA, and Glutamine Levels and Associations with Recent Drinking in Treatment‐Naïve Individuals with Alcohol Use Disorder Versus Light Drinkers

Abstract: Background-Proton Magnetic Resonance Spectroscopy (1 H-MRS) studies have demonstrated abnormal levels of a variety of neurometabolites in inpatients/outpatients with Alcohol Use Disorder (AUD) following acute alcohol withdrawal relative to healthy controls. In contrast, few studies have compared neurometabolite levels between less severe, treatment-naïve AUD individuals and light drinkers or related them to recent alcohol consumption. The present study compared neurometabolite levels between treatment-naïve AU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
32
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 25 publications
3
32
2
Order By: Relevance
“…Unlike Prisciandaro et al, 20 no differences were found in glutamine levels between AUD and light drinkers at the initial scan. We concentrated initial speculation concerning why this finding did not replicate in the present study on the primary difference between the two studies: number of days since last drink at baseline.…”
Section: Discussioncontrasting
confidence: 59%
See 3 more Smart Citations
“…Unlike Prisciandaro et al, 20 no differences were found in glutamine levels between AUD and light drinkers at the initial scan. We concentrated initial speculation concerning why this finding did not replicate in the present study on the primary difference between the two studies: number of days since last drink at baseline.…”
Section: Discussioncontrasting
confidence: 59%
“…Twenty‐three individuals with AUD and 12 demographically matched LD were recruited from community advertisements; an additional eight LD participants (ie, females with relatively fewer years of education) were selected from Prisciandaro and colleagues' LD sample 20 to demographically match LD and AUD participants for baseline group comparisons. AUD participants from the present study and Prisciandaro et al (2018) also appear in a concurrently published investigation of brain glycine levels in AUD participants 21 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although glutamate levels at the earlier time point were inversely associated with cognitive task performance, improved cognitive function was not related to any changes in glutamate or indeed other MRS markers [creatine, N -acetylaspartate (NAA), choline, and GABA]. Similarly, lower glutamine levels have been found in alcohol-dependent individuals who are still drinking, though breathalyzed negative at the time of the scan, compared with light drinkers (111). An inverse relationship between glutamate, but not glutamine, levels and number of heavy drinking days has been reported in ACC of alcohol-dependent participants but not light drinkers (18).…”
Section: Brain Imaging Of Alcohol Detoxification In Humansmentioning
confidence: 99%